HMGA1 deficiency: a pathogenic link between tau pathology and insulin resistanceResearch in context - Maria Mirabelli; Eusebio Chiefari; Biagio Arcidiacono; Alessandro Salatino; Angelo Pascarella; Maurizio Morelli; Sara C. Credendino; Francesco S. Brunetti; Anna Di Vito; Adelaide Greco; Vincent Huin; Ferdinando Nicoletti; et al. (EBioMedicine)
Summary: Background: Growing evidence links tau-related neurodegeneration with insulin resistance and type 2 diabetes (T2D), though the underlying mechanisms remain unclear. Our previous research identified HMGA1 as crucial for insulin receptor (INSR) expression, with defects in the HMGA1 gene associated with insulin resistance and T2D. Here, we explore HMGA1 deficiency as a potential contributor to tauopathies, such as Alzheimer's disease (AD), and its connection to insulin resistance. Methods: Immunoblot analyses, protein-DNA interaction studies, ChIP-qPCR, and reporter gene assays were conducted in human and mouse neuronal cell models. Tau immunohistochemistry, behavioural studies, and brain glucose metabolism were analysed in Hmga1-knockout mice. Additionally, a case–control study investigated the relationship between HMGA1 and tau pathology in patients with tauopathy, carrying or not the HMGA1 rs146052672 variant, known to reduce HMGA1 protein levels and increase the risk of insulin resistance and T2D. Findings: We show that HMGA1 regulates tau protein expression primarily through the specific repression of MAPT gene transcription. In both human neuronal cells and primary mouse neurons, tau mRNA and protein levels were inversely correlated with HMGA1 expression. This inverse relationship was further confirmed in the brain of Hmga1-knockout mice, where tau was overexpressed, INSR was downregulated, and brain glucose uptake was impaired. Additionally, the rs146052672 variant was more common in patients with tauopathy (12/69, 17.4%) than in controls (10/200, 5.0%) (p = 0.001), and carriers of this variant exhibited more severe disease progression and poorer therapeutic outcomes. Interpretation: These findings suggest that HMGA1 deficiency may drive tau pathology, linking tauopathies to insulin resistance and providing new insights into the relationship between metabolic and neurodegenerative disorders. Furthermore, our observation that over 17% of individuals with tauopathy exhibit a deficit in HMGA1 protein production could have significant clinical implications, potentially guiding the development of therapeutic strategies targeting this specific defect. Funding: See acknowledgements section.